STRATEGI KOMUNIKASI INTERNAL DALAM SOSIALISASI BUDAYA BARU (STUDI KASUS RUMAH SAKIT BAKTI TIMAH PANGKALPINANG) - Mimi Sumarni; Henni Gusfa (Universitas Mercu Buana, 2018)
Corporate culture as a system of shared meaning shared by members that differentiates an organization from other organizations. The success of an organization is absolutely related to a growing and prevailing culture within the organization, the success in building a culture in accordance with the vision, mission and character as well as the behavior of the members greatly determine the ability of the organization to survive and even win the competition in other organizations. This study aims to describe and examine in depth the internal communications strategy in designing the hospital culture and to see the results of cultural demensi and internal communication in the hospital. Internal communication strategy is a structured plan to clarify pressing to members of the organization that includes Strategic analysis, Strategic intent, Strategic Action. The paradigm of this research is Kontruktivis this paradigm saw that the reality is the result of construction or formation of the man himself and hold that the knowledge is not only the result of the construction of subjective thinking studied. This study uses a qualitative case study method which is one of the research strategies to develop an in-depth analysis with the main problem of how internal communication strategy in designing corporate culture at Bakti Pahang Pangkalpinang Hospital.Keywords: Corporate Culture, Internal Communication Strategy, Bakti Timah Hospital.